Computational analysis of the structural-functional dynamics of a Co-receptor proteoglycan - Francesco Tavanti; Francesco Tavanti; Francesco Tavanti; Giorgia Brancolini; Roberto Perris; Roberto Perris (Frontiers in Molecular Biosciences)
Nerve-Glial Antigen 2/Chondroitin Sulphate Proteoglycan 4 (NG2/CSPG4) is the largest membrane-intercalated cell surface component of the human proteome known to date. NG2/CSPG4 is endowed with the capability of engaging a myriad of molecular interactions and exert co-receptor functions, of which primary ones are sequestering of growth factors and the anchoring of cells to the extracellular matrix. However, the nature of the interactive dynamics of the proteoglycan remains veiled because of its conspicuous size and structural complexity. By leveraging on a multi-scale in silico approach, we have pioneered a comprehensive computational analysis of the structural-functional traits of the NG2/CSPG4 ectodomain. The modelling highlights an intricate assembly of β-sheet motifs linked together by flexible loops. Furthermore, our in silico predictions highlight that the previously delineated D1 domain may consistently remain more accessible for molecular interplays with respect to the D2 and D3 domains. Based on these findings, we have simulated the structural mechanism through the proteoglycan may serve as a co-receptor for growth factor FGF-2, showing that NG2/CSPG4 bends towards the receptor FGFR-1 for this growth factor and confirming the previously hypothesized trimeric complex formation promoted by FGF-2 dimers bridging the FGFR-1-proteoglycan interaction. The Chondroitin Sulphate Proteoglycan 4 is a large multi-domain transmembrane protein involved in several biological processes including pathological conditions. Despite its importance, it has never been studied at the atomistic level due to its large size. Here, we employed a multi-scale computer simulations approach to study its three-dimensional structure, its movements and co-receptor properties, showing that it can serve as mediator in the growth factor signaling process.